Body Language and Its Universal Meaning: the Interpretation of Body Language in the Little Black Book Film - Lalu Suhirman (Center of Language and Cultural Studies, 2019)
This study aims to examine body language, namely facial expressions that appear in film scenes entitled 'Little Black Book'. Therefore, this study discusses two research questions: 1) what conventional meaning is expressed by the facial expressions of central figures in 'Little Black Book' film? 2) what are the forms and patterns of body language that carry important messages besides facial expressions in 'Little Black Book' film? This study uses a qualitative approach to analyze data. The data source of this research is the film